1996
DOI: 10.1037/0022-3514.71.2.390
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in intuitive–experiential and analytical–rational thinking styles.

Abstract: Two studies provide evidence for the reliability and validity of a new self-report measure of individual differences in intuitive-experiential and analytical-rational thinking based on cognitive-experiential self-theory (CEST). The Rational-Experiential Inventory (REI) was constructed to measure the 2 independent processing modes with a modified Need for Cognition Scale (NFC, J.T. Cacioppo & R.E. Petty, 1982) and a new scale, Faith in Intuition (FI). In Study 1, a factor analysis yielded 2 orthogonal factors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

65
1,528
2
48

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,467 publications
(1,677 citation statements)
references
References 30 publications
65
1,528
2
48
Order By: Relevance
“…Cognitive Experiential Self Theory (CEST) is the outcome of a line of work undertaken by Epstein and his colleges (e.g. Donovan & Epstein, 1997, Epstein, Pacini, Denes-Raj, & Heier, 1996DenesRaj & Epstein, 1994). CEST is a broad theory of personality that supposes people process information through two independent but parallel cognitive systems, one a preconscious experiential/intuitive system and the other a conscious rational/analytical system .…”
Section: Cognitive Experiential Self Theory (Cest)mentioning
confidence: 99%
See 4 more Smart Citations
“…Cognitive Experiential Self Theory (CEST) is the outcome of a line of work undertaken by Epstein and his colleges (e.g. Donovan & Epstein, 1997, Epstein, Pacini, Denes-Raj, & Heier, 1996DenesRaj & Epstein, 1994). CEST is a broad theory of personality that supposes people process information through two independent but parallel cognitive systems, one a preconscious experiential/intuitive system and the other a conscious rational/analytical system .…”
Section: Cognitive Experiential Self Theory (Cest)mentioning
confidence: 99%
“…It emphasizes ''vibes,'' emotions, and stereotypical thinking from past events (Epstein, 1991). The experiential system is also associated with solving problems that rely on life lessons and experience that elude articulation and logical analysis (Epstein, 1991) and is particularly prone to logical shortcuts or heuristics (Denes-Raj & Heier, 1996). In his early work, Epstein demonstrated that the experiential system is credited with the ability to form interpersonal relationships, creative thoughts and emotionality (Epstein, 1991).…”
Section: Cognitive Experiential Self Theory (Cest)mentioning
confidence: 99%
See 3 more Smart Citations